Influence of Job Stress and Nurse-Physician Collaboration on Job Satisfaction of Nurses and Doctors in Ekiti State, Nigeria. - Samuel, Olatunji; Mokuolu, Bolade Olubunmi (Advances in Social Sciences Research Journal, 2014)
The study examined the underlying factors that influence job satisfaction of nurses and doctors in Ekiti state of Nigeria. One hundred and ninety one professionals, comprising one hundred and two nurses and eighty nine doctors responded to the Perceive Stress Scale, Collaboration and Satisfaction about Care Decisions, and Minnesota Satisfaction questionnaire. The results using the 2X2 Analysis of Variance showed that job stress has effect on job satisfaction of the respondents [F (1,187) =161.64, p<.01]. The effect of nurse-physician collaboration on job satisfaction of the respondents was also confirmed. [F (187) = 22.28, p<.01]. There is also a significant interaction effect of job stress and nurse-physician collaboration on job satisfaction of the respondents [F (187) = 6.89, p<.01]. Stress managements strategies and collaborative practice were suggested.